2019
DOI: 10.1159/000502957
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Baked Milk and Egg Challenge in Cow’s Milk and Hen’s Egg Allergy: Can Tolerance Be Predicted with Allergen-Specific IgE and Prick-to-Prick Test?

Abstract: <b><i>Background:</i></b> Adding baked food into the diets of patients with cow’s milk allergy (MA) and hen’s egg allergy (EA) has several benefits. <b><i>Objective:</i></b> We aimed to determine baked and unbaked food tolerance and evaluate the effectiveness of laboratory findings on the prediction of baked and unbaked food tolerance in patients with MA and EA. <b><i>Methods:</i></b> Clinical outcomes of the patients with MA and EA who ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Research has shown that 65-83% of children with milk allergies can safely consume baked-milk products. [8][9][10][16][17][18][19][20][21][22][23] Notably, Cherkaoui et al 21 detected a positive rate of 23% in patients with CM allergy in oral provocation tests performed with baked milk. Nowak-Wegrzyn et al, 8 who used muffins and waffles containing baked milk, reported an identical positive rate of 23%.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that 65-83% of children with milk allergies can safely consume baked-milk products. [8][9][10][16][17][18][19][20][21][22][23] Notably, Cherkaoui et al 21 detected a positive rate of 23% in patients with CM allergy in oral provocation tests performed with baked milk. Nowak-Wegrzyn et al, 8 who used muffins and waffles containing baked milk, reported an identical positive rate of 23%.…”
Section: Discussionmentioning
confidence: 99%
“…The food that causes IgE-mediated food allergy varies according to the nutritional habits of the population. The most common food-allergy type in our country is the allergies emerging after cow's milk and eggs (7,8). Milk and egg allergy in children is a common cause of anaphylactic reactions.…”
Section: Msdmentioning
confidence: 99%
“…In the present study, we found that children with persistent milk allergies were more likely to have persistent EAs, which, in part, coincided with study from Sicherer 20 , which suggests that persistent milk allergy may be used as a time predictor of EA tolerance. Kose et al 24 have conducted a retrospective study and found that at the end of 6 months of consuming baked hen's egg (BE), the scrambled egg tolerance was negatively associated with EW-specific IgE levels, EW SPT, and the EW prick-to-prick test (PTP). EW PTP was the most significant parameter 22 .…”
Section: Risk Factors For the Outcome Of Eamentioning
confidence: 99%